THE KITE RUNNER OF KHALED HOSSEINI - Miswari, Miswari (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2018)
It is necessary for the writer to extract the description upon the contents of character analysis. The result of study might have produced the writer to expose the descriptive of the characters. The writer got starting to dig some advantages of describing the characters in the novel of ‘The Kite Runner' through the story that is taking us from Afghanistan in the final days of the monarchy to the present, ‘The Kite Runner' is the unforgettable, beautifully told story of the friendship between two boys growing up in Kabul. The Kite Runner is a novel about friendship, betrayal, and the price of loyalty. It is about the bonds between fathers and sons, and the power of their lies. Written against a history that has not been told in fiction before, The Kite Runner describes the rich culture and beauty of a land in the process of being destroyed. But with the devastation, Khaled Hosseini also gives us hope: through the novel's faith in the power of reading and storytelling, and in the possibilities he shows for redemption.